The dynamics of deforestation and economic growth in the Brazilian Amazon - Andersen, Lykke E. (Press Syndicate of the University of Cambridge ; Cambridge University Press, 2002)
Making use of a uniquely rich data set the authors analyze the ecological and economic impacts of a range of policies and examine whether the economic benefits of land clearing surpass the ecological costs. Their conclusions are surprising.